Persepsi Warga Terhadap Budaya 5S dalam Pendayagunaan Sampah Daur Ulang di RW 02 Manyaran Semarang - Septa Wiki Dwi Cahyani; Vamelia Aurina Pramandhani (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study conducted to explore residents' perceptions of 5s culture (Seiri, Seiton, Seiso, Seiketsu, Shitsukei) in recycling waste utilization activities in the Family Empowerment and Welfare Group (PKK) RW 02 Manyaran Village, Semarang. This activity was executed in order to introduce 5S working principle originating from Japan, which can help create a more organized, efficient, and hygienic work environment. By using the 5s approach, PKK members are expected to manage organic waste more effectively, reduce waste entering landfills, and support the establishment of a hygienic and visual spelling setting. Method used was a descriptive qualitative approach, with interviews with 13 PKK members of RW 02 Manyaran Semarang. The results demonstrated a positive impact, especially in the aspects of Seiri, Seiso, and Shitsukei. Residents have understood the importance of sorting, maintaining cleanliness, and discipline in waste recycling activities. However, Seiton and Seiketsu aspects remain suboptimal due to inadequate facilities and the absence of written procedures.